Self-control exertion and caffeine mouth rinsing: Effects on cycling time-trial performance. (March 2021) - Boat, Ruth; Williamson, Ollie; Read, Jake; Jeong, Yoon Hyuk; Cooper, Simon B.
Abstract: Objectives: The exertion of self-control has been associated with impaired performance on subsequent physical tasks also requiring self-control. However, the effect in well-trained individuals, and of nutritional intervention strategies to reduce the impact of self-control exertion are unknown. This study, therefore, explored the effect of self-control exertion on endurance performance, and pacing strategies, in well-trained individuals. A further aim was to examine the potential for a caffeine mouth rinse to attenuate any decrements in performance due to self-control exertion. Method: Following familiarization, fifteen trained male cyclists completed four simulated 10 km cycling time-trials on a cycle ergometer. Prior to each time-trial, participants completed a congruent Stroop task, or an incongruent Stroop task, to manipulate self-control. They also received either a caffeine (containing 40 mg of dissolved caffeine) or placebo mouth-rinse prior to, and every 2 km during, the cycling time-trial. The participants' performance time, subjective measures (perceived pain, motivation, task importance, and RPE), heart rate, and blood lactate concentration were recorded throughout the time-trials. Data were analysed using three-way (self-control*caffeine*split time) repeated measures ANOVA. Results: There was no effect of self-control or caffeine on overall 10 km performance time (all p > 0.05). However, following self-control exertion, split time was significantly slower at 3 km ( p = 0.031) and 5 km ( p = 0.034), and tended to be slower at 1 km ( p = 0.088) and 7 km ( p = 0.078). There was no effect of the caffeine mouth rinse, nor did this interact with self-control, to affect split times (all p > 0.05). Prior self-control exertion and a caffeine mouth rinse did not influence perceptions of pain, motivation, and task importance in well-trained individuals (all p > 0.05). Conclusions: Findings suggest that prior self-control exertion affects self-regulatory pacing strategies during the first 7 km of a 10 km cycling time-trial, in well-trained individuals. However, caffeine mouth rinsing does not attenuate the effects of self-control exertion on subsequent endurance performance. Highlights: Self-control exertion affected pacing strategies during a cycling time-trial. No overall effect of a caffeine mouth rinse on cycling time-trial performance. A caffeine mouth rinse did not attenuate the effects of self-control on pacing. Perceived pain and motivation were unaffected in well-trained cyclists.